Behavioral Implications of Taxation: A Reply. - Crumbley, D. Larry (The Accounting Review, 1974)
Abstract This article presents response from the author to the comments on his article "Behavioral Implications of Taxation," published in the October 1973 issue of the journal "The Accounting Review." It was argued that the author's article did not always maintain a clear distinction between ex ante and ex post research. This issue is basically a semantical difference. The author agrees that behavioral research can be ex ante and ex post. Many specific research methodologies incorporate both ex ante and ex post research. There is no way to know what are the best paths to follow as the body of knowledge is being developed. Tax analysis research would, of course, include both ex post and ex ante research. The 1973 AAA's Committee on Federal Income Taxes indicates that tax research consists of two types: tax compliance and planning research and tax analysis research. The first type refers simply to finding a competent and professional conclusion to a tax problem. It includes such subsets as tax return preparation or review, tax minimization and deferral, and practice before the U.S. Internal Revenue Service and the Tax Court. The second type of research goes beyond this fact-oriented research and focuses upon the data-gathering stage in the testing of tax hypotheses.